2018
DOI: 10.1155/2018/5891531
|View full text |Cite
|
Sign up to set email alerts
|

The Increment of Choroidal Thickness in Euthyroid Graves’ Ophthalmopathy: Is It an Early Sign of Venous Congestion?

Abstract: Objective Clinical manifestations of Graves' ophthalmopathy (GO) are caused by the overcompression of orbital tissues within the restricted orbital bone cavity. Impaired ocular blood flow may disrupt the retinal microstructure and functions. In this study, we aimed to investigate the macular and choroidal thickness changes in GO compared with healthy subjects. Materials and Methods The study group comprised 50 adult patients with previously diagnosed Graves' disease with ophthalmopathy who were on antithyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
6
1
2
Order By: Relevance
“…Choroid is the most vascular ocular structure and has been instrumental in the assessment of various ocular diseases . However, information on choroidal changes in TAO is limited . This current study found thicker choroid in patients with TAO compared to healthy subjects over the macula but not the peripapillary regions.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…Choroid is the most vascular ocular structure and has been instrumental in the assessment of various ocular diseases . However, information on choroidal changes in TAO is limited . This current study found thicker choroid in patients with TAO compared to healthy subjects over the macula but not the peripapillary regions.…”
Section: Discussioncontrasting
confidence: 41%
“…15 However, information on choroidal changes in TAO is limited. 6,7,16 This current study found thicker choroid in patients with TAO compared to healthy subjects over the macula but not the peripapillary regions. Among TAO eyes, thinner subfoveal choroidal thickness was significantly associated with older age, longer axial length, worse exophthalmos and lower VA. To our knowledge, peripapillary choroidal thickness in TAO patients was reported for the first time.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Bruscolini et al 18 also observed higher subfoveal choroidal thickness values in Graves’ ophthalmopathy patients and reported a significant direct correlation between choroidal thickness and CAS score as well as with proptosis level measured by Hertel exophthalmometry. In a similar study, Cagiltay et al 19 included euthyroid patients in the study to eliminate the effect of hyperthyroidism on choroidal circulation and evaluated disease activity with vision, inflammation, strabismus, and appearance (VISA) score. Mean, subfoveal, and temporal choroidal thicknesses were higher in the study group and mean choroidal thickness was positively correlated with VISA score.…”
Section: Discussionmentioning
confidence: 99%